Security Considerations in Wireless Ad-hoc Networks Using Commitment Schemas - Kiranbabu, M.; Prasad, D. Varun (International Journal of Emerging Trends in Science and Technology, 2014)
The open nature of the wireless medium leaves it vulnerable to intentional interference attacks, typically referred to as jamming. This intentional interference with wireless transmissions can be used as a launch pad for mounting Denial-of-Service attacks on wireless networks. Although the attack models are classified as both external and internal with the latter being more serious because the â€œalways-onâ€ strategy employed in external model has several disadvantages. In an internal threat model an adversary is assumed to be aware of network secrets and the implementation details of network protocols at any layer in the network stack. The adversary exploits his internal knowledge for launching selective jamming attacks in which specific messages of â€œhigh importanceâ€ are targeted. Although RREQ, RREP, RERR, RREP-ACK are primary Message Formats in reactive protocols, the adversary selectively targets RREQ and RREP packets in the network to launch jamming attacks. Prior approaches concentrated on using commitment schemes that are cryptographic primitives to hide the RREQ and RREP packets from the purview of the adversary. These approaches being successful, I propose to use them along with intrusion detection techniques for identifying compromised routers to increase overall network security significantly by marginalizing the working boundaries of an adversary, thus risking exposure. A practical implementation validates our claim.